x2+9x+1=-7

Simple and best practice solution for x2+9x+1=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2+9x+1=-7 equation:



x2+9x+1=-7
We move all terms to the left:
x2+9x+1-(-7)=0
We add all the numbers together, and all the variables
x^2+9x+8=0
a = 1; b = 9; c = +8;
Δ = b2-4ac
Δ = 92-4·1·8
Δ = 49
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{49}=7$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-7}{2*1}=\frac{-16}{2} =-8 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+7}{2*1}=\frac{-2}{2} =-1 $

See similar equations:

| q^2(+3-11q^2*20)=0 | | 2-q(11/10)+q^2(3/20)=0 | | 2-(11q/10)+(3q^2/20)=0 | | (4)/(9)m=-24 | | q(2-3q)=40 | | 4(1/2x+3/4)=x-1.5 | | 2(r+9=24 | | (7/2t)−2=4+7t | | 0=4x-3=11 | | 81^-x-12=729^5x+10 | | 5(p+17)=2p-3 | | -3x+24=-8x-11 | | 5x-44=-2x+3 | | 28=2(x-2)-8x | | -28=2(x-2)-18 | | 3v=-0.4 | | 4^5x=1/16 | | 3x^-4-8x^-2+4=0 | | t6+12=24 | | 4h-7h=17 | | 5(3)+5y=10 | | w2+5=10 | | 15x+-17=1x+-6 | | -20x+4=-1x+-10 | | 34=3(7v-2) | | -3x+8=-6x+-6 | | X+2x-1°+x+5°=360° | | 3(x—7)=2x+4 | | 12x+5–5x–3=13x+12 | | x–26=29 | | 3x-6(x+4)+10=-2 | | 8(2+h)=96 |

Equations solver categories